Efforts to Increase Regional Retribution in Manokwari Regency 2016-2020 (Analysis of Achievements and Constraints) - Mansim, Naftali; Situmorang, Elina R; Tewernusa, Ketysia I (AIBPM Publisher, 2024)
The government's efforts to increase regional levy revenues are the focus of this research. This is due to the still very low contribution of regional levies in Original Regional Income. Regional Retribution Data was obtained from the Regional Asset and Financial Management Agency Report for the 2016-2020 period, while the government's efforts were analyzed through in-depth interviews with sources. The government's efforts to increase levy revenues are still very low, namely limited to providing regional regulations without providing standard operating procedures and also not carrying out major monitoring of levy achievements